2022
DOI: 10.3389/fonc.2022.835582
|View full text |Cite
|
Sign up to set email alerts
|

A Geriatric Assessment Intervention to Reduce Treatment Toxicity Among Older Adults With Advanced Lung Cancer: A Subgroup Analysis From a Cluster Randomized Controlled Trial

Abstract: IntroductionMore older adults die from lung cancer worldwide than breast, prostate, and colorectal cancers combined. Current lung cancer treatments may prolong life, but can also cause considerable treatment-related toxicity.ObjectiveThis study is a secondary analysis of a cluster-randomized clinical trial which evaluated whether providing a geriatric assessment (GA) summary and GA-guided management recommendations can improve grade 3-5 toxicity among older adults with advanced lung cancer.MethodsWe analyzed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Second, future work should incorporate a comprehensive geriatric assessment as part of standard practice before initiating treatment and collect patient-reported outcomes afterward . This can assist in making treatment decisions more patient centered and substantially decrease treatment-related toxic effects . Our study focused on survival; however, it is also critical to assess temporal trends in QOL, including physical and financial burden.…”
Section: Discussionmentioning
confidence: 99%
“…Second, future work should incorporate a comprehensive geriatric assessment as part of standard practice before initiating treatment and collect patient-reported outcomes afterward . This can assist in making treatment decisions more patient centered and substantially decrease treatment-related toxic effects . Our study focused on survival; however, it is also critical to assess temporal trends in QOL, including physical and financial burden.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, such as Corre et al [44], have demonstrated similar results in advanced non-small-cell lung cancer, with CGA-based individualized treatment failing to improve treatment outcomes but slightly reducing treatment toxicity. Mohile et al [45] report that older patients with advanced cancer undergoing CGA (incurable solid tumors or lymphoma) experience less grade 3-5 toxicity than their non-CGA counterparts. These studies highlight the importance of CGAguided interventions to improve outcomes, although more speci c studies are needed to determine how CGA-tailored treatment can reduce toxicity for older individuals with lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Over 3 months, patients in the intervention group also had fewer falls (12%) than patients in the usual group (21%; adjusted RR, 0.58 [95% CI, 0.40 to 0.84]; P = .0035), and had more medications discontinued (mean adjusted difference, 0.14 [95% CI, 0.03 to 0.25]; P = .015). Two recently published secondary analyses of data from GAP70+ reported, respectively, a significantly lower proportion of stage III and IV patients with lung cancer who experienced grade 3-5 toxicity in the intervention arm versus usual care (53.1% v 71.6%; P = .01) 24 ; and, among 623 patients from GAP70+ with follow-up Patient-Reported Outcomes Common Terminology Criteria for Adverse Events (PRO-CTCAE) data, fewer patients in the GA intervention arm reported grade ≥2 symptomatic toxicity compared to usual care patients (overall: 88.9% v 94.8%; P = .035; core symptoms: 83.4% v 91.7%; P = .001). 25…”
Section: Updated Recommendationsmentioning
confidence: 98%
“…A total of 15 publications met eligibility criteria and form the evidentiary basis for the guideline recommendation pertaining to Clinical Question 1. 3,4,[14][15][16][17][18][19][20][21][22][23][24] The identified publications include the respective primary reports of nine RCTs evaluating GAM 3,4,[14][15][16][17][18][19][20] ; four reports of secondary analyses of data from the primary RCTs [23][24][25][26] ; one systematic review of GA studies 22 ; and one systematic review of GA studies with meta-analysis. 21 The identified RCTs were published between 2020 and 2022.…”
Section: Characteristics Of Studies Identified In the Literature Sear...mentioning
confidence: 99%